Analysis of Students' 6C Skills Based on the Implementation of the Independent Curriculum on Ecosystem Material - Aura Andyta; Hasruddin (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
This study investigates the development of 21st-century skills (6C) critical thinking, creativity, collaboration, communication, character, and citizenship among tenth grade students of SMA Swasta  PAB  8  Saentis  through  the  implementation of  the Independent Curriculum in the ecosystem topic. A quantitative descriptive approach was employed, utilizing tests, questionnaires, and classroom observations involving 61 randomly selected students from five classes. The results indicate that critical thinking and creativity skills reached an average score of 44%, categorized as fair, whereas communication (88%), collaboration (83%), character (84%), and citizenship (83%) were classified as very good. Observation data also revealed that collaboration and creativity skills averaged 70%, falling into the good category. These findings suggest that the Independent Curriculum has effectively fostered students social and character skills, yet cognitive dimensions such as critical thinking and creativity remain underdeveloped. To address this gap, the study recommends the consistent application of project-based and collaborative learning strategies as  a  means  to  strengthen analytical abilities and enhance students creative thinking in a more comprehensive manner.